2014
DOI: 10.12988/ams.2014.46439
|View full text |Cite
|
Sign up to set email alerts
|

Energy characterization of residual biomass in Mediterranean Area for small biomass gasifiers in according to the European Standards

Abstract: Biomass is one of the most easily available Renewable Energy Sources (RES) which can be converted into some useful forms of energy through different processes; among them the gasification technology is a particularly efficient method. Each biomass, has to be analyzed in order to find out if it is suitable for a specific conversion. 6622 Sonia Castellucci et al. In this work some typical biomass of Mediterranean Area, with specific regard to residual ones, are analyzed according to the European Standards, in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The C/N ratio is an important parameter in the study of thermochemical processes, which is useful in determining the most suitable energy conversion process. It was discovered that higher ratio values indicate a more suitable biomass for the gasification process [7,15]. However, lower values of this ratio in the biomasses confirm that the development of NOX would be minimised in the pyrolysis [28].…”
Section: Ultimate Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The C/N ratio is an important parameter in the study of thermochemical processes, which is useful in determining the most suitable energy conversion process. It was discovered that higher ratio values indicate a more suitable biomass for the gasification process [7,15]. However, lower values of this ratio in the biomasses confirm that the development of NOX would be minimised in the pyrolysis [28].…”
Section: Ultimate Analysismentioning
confidence: 99%
“…Several authors identified a VS range for diverse biomasses of 3.93 to 96.96% [10,20,23,24,28,[35][36][37][38], The VS content found in Laminaria digitate, Ascophyllum nodosum and Chaetomorpha macroalgaes was 25.5, 63.3 and 84.3%, respectively [39] while Spirulina platensis microalgae contained 77.96% [17], and Chlorella vulgaris microalgae 84.3%, [18]. The presence of ash in biomasses has appeared in the range between 0.34 and 52.39% [7,9,10,20,24,28,35,36,39,40], for Laminaria digitate, Ascophyllum nodosum and Chaetomorpha macroalgaes are 59.9, 31.8 and 67.6%, respectively [39]. Additionally, for Spirulina platensis and Chlorella vulgaris microalgae it was observed 10.14 and 5.3% [17,18].…”
Section: Proximate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Because of being source of nutrients, wastewater can greatly reduce the production cost of microalgae; hence, growth of microalgae in wastewater provides biomass and simultaneous bioremediation of wastewater [4]. Microalgae are single-celled or colonial photosynthetic organisms that are available in large amount and in many different environments including rivers, lakes, oceans and soils [5,6]. These organisms synthesize lipids, carbohydrate and proteins, which are used for producing valueadded products [7].…”
Section: Introductionmentioning
confidence: 99%
“…The availability in large amounts in different areas and environments is a significant advantage of using residual biomass. In addition, it increases the economic value of waste and reduces environmental impacts of its disposal [4]. Interesting approaches have been studied for agro-forestry lignocellulosic biomass in the last years due to the needs of alternative sources for energy and materials production [5].…”
Section: Introductionmentioning
confidence: 99%